2015
DOI: 10.1083/jcb.201508093
|View full text |Cite
|
Sign up to set email alerts
|

Discs of mammalian rod photoreceptors form through the membrane evagination mechanism

Abstract: Ultrastructural analysis of membrane organization in mouse rod cells demonstrates that new photoreceptor discs are contiguous evaginations of the outer segment plasma membrane, thereby resolving the debate of whether discs are formed through membrane evagination or intracellular vesicular fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
124
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 33 publications
4
124
0
1
Order By: Relevance
“…This remarkable rate of membrane turnover and RPE phagocytosis is balanced by daily disc regeneration, but an understanding of the cellular process of regeneration of new photoreceptor discs has been poorly understood. Recently, new electron microscopy methodologies have revealed that OS discs are formed through a process of membrane evagination and indicate a highly regulated and ordered process at play in building photoreceptor discs (11)(12)(13). Rhodopsin is not only a photoreceptor but is a required structural component for disc membrane formation.…”
Section: Docosahexaenoic Acid (Dha)mentioning
confidence: 99%
See 1 more Smart Citation
“…This remarkable rate of membrane turnover and RPE phagocytosis is balanced by daily disc regeneration, but an understanding of the cellular process of regeneration of new photoreceptor discs has been poorly understood. Recently, new electron microscopy methodologies have revealed that OS discs are formed through a process of membrane evagination and indicate a highly regulated and ordered process at play in building photoreceptor discs (11)(12)(13). Rhodopsin is not only a photoreceptor but is a required structural component for disc membrane formation.…”
Section: Docosahexaenoic Acid (Dha)mentioning
confidence: 99%
“…The early postnatal reduction in OS length without photoreceptor cell death was a striking feature of Mfsd2a KO retinas. The OS contains photoreceptor disc membranes that form through membrane biogenesis in the IS (11)(12)(13), occurring on a daily basis to balance photoreceptor disc turnover at the distal OS via phagocytosis by the RPE (10). It can be imagined that this high level of membrane biogenesis to build OS discs would apply unique metabolic demands on the retina.…”
Section: Srebp1cmentioning
confidence: 99%
“…The alternative hypothesis (ii) rests on the fact that a number of basal discs (and possibly distal discs) of the rod OS are not closed and internalized in the OS, but rather like classic cone discs are contiguous with the plasma membrane (61,62) (Fig. 5).…”
Section: Estimating the Spring Constant Of An Elementary Rod Os Elasticmentioning
confidence: 99%
“…This realization, combined with evidence of vesicles in the connecting cilium seen in electron micrographs, has been taken to support the model that vesicles are actively transported through the connecting cilium and generate nascent discs by membrane fusion at the base of the outer segment (Chuang et al, 2007(Chuang et al, , 2015. Ding et al (2015) addressed these competing hypotheses with two distinct approaches. First, they treated sections of retinas of mice perfused with a membrane-staining mixture of tannic acid and uranyl acetate and performed EM.…”
mentioning
confidence: 98%